Factors influencing wildmeat trade in Guyana and expected changes in the context of the oil-related development prospects - Franciany Braga-Pereira; Anupana Puran; David Oswin; Evi AD Paemelaere; Nathalie van Vliet (Global Ecology and Conservation)
The recent offshore oil discovery in the Guiana Shield is expected to bring about significant changes to the area, such as increased GDP per capita, infrastructure development, and urbanization. The potential impact on the wild meat trade depends on factors influencing its demand and provision. Through interviews and group discussions with trade chain stakeholders in all towns of Guyana, we evaluate wildmeat trade sector and explored predicted changes on it in 2033 with the prospects for short term oil-related development. The most traded species in Guyana included paca, white-lipped peccary, deer, tapir and capybara and a total of 38.46 % (5 out of 13) of the taxa being traded is classified as threatened of extinction. Regions with higher population size and GDP per capita, are the main trade hubs for wildmeat. Access to improved preservation methods (e.g. freezers) and motorized transportation options (eg.: boat with engines and vehicles) significantly influence higher volumes of wildmeat traded. The economic growth anticipated in Guyana is expected to boost population growth and, by the same time, wildmeat demand in urban areas. Concomitantly, with improved infrastructure and increased access to electricity, wildmeat provision will be facilitated across a wider catchment area. Based on the assumption that cultural patterns shaping wildmeat demand and environmental regulations will likely not change at the same rapid path as economic growth in the next ten years, we predict wildmeat trade volumes to increase to 10,280 tons/year by 2033. We identify three main opportunities to ensure a sustainable wildmeat sector in the context of the economic boom: First, the sector requires to be well regulated through a licensing and a quota system that can be adequately enforced. Second, efforts to curve demand on the Coast need to be strengthened based on well designed and culturally adapted behaviour change campaigns. Third, local communities and indigenous people need to be empowered to protect and conserve their territories and wildlife resources, in particular with the authority to exclude illegal hunters.